PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PERINGKAT SURAT UTANG PERUSAHAAN DI INDONESIA - Setyaningrum, Dyah (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
This research investigated whether corporate governance mechanism affects the firm 's bond rating in Indonesia. Specifically, investigation on whether corporate governance components, which are represented by ownership structure and influence, financial transparency and disclosure and board structure, affect the firm s bond rating. This research used several corporate governance mechanisms developed by Bursa Efek Jakarta and bond rating classification developed by Pefindo and Kasnic. Ordered logit model is selected to test the research problem. Using firm s characteristic as controlling variable, this research found that the firm s bond rating is: (1) negatively associated with the number o f block holders that own at least 5% ownership on the firm; (2) positively associated with percentage o f institutional ownerships; (3) positively associated with the size o f public accounting firm, and (4) positively associated with existence o f audit committee. The relationship between percentage o f insider, board size and percentage o f independent board with bond rating is not supported by empirical data.